The relationship between preoperative anxiety levels and vasovagal incidents during the administration of spinal anesthesia - Ekinci,Mürsel (2017)
Abstract Background: It was aimed to investigate the relationship between preoperative anxiety and vasovagal symptoms observed during the administration of spinal anesthesia in patients undergoing surgery in the perianal and inguinal regions. Methods: The study included patients with planned surgery for inguinal hernia repair, anal fissure, hemorrhoid and pilonidal sinus excision. The study included a total of 210 patients of ASA I-II, aged 18-65 years. Patients were evaluated in respect of demographic characteristics, smoking and alcohol consumption, ASA grade and educational level. Correlations were evaluated between the number of attempts at spinal anesthesia and anesthesia history with vasovagal symptoms and educational level, gender, smoking and alcohol consumption and anesthesia history with anxiety scores. The instant (transient) state anxiety inventory part of the Transient State/Trait Anxiety Inventory (State Trait Anxiety Inventory - STAI) was used to determine the anxiety levels of the participants. Clinical findings of peripheral vasodilation, hypotension, bradycardia and asystole observed during the administration of spinal anesthesia were recorded. Results: Vasovagal incidences during the administration of spinal anesthesia were seen to increase in cases of high anxiety score, male gender, and an absence of anesthesia history. Educational level and the number of spinal needle punctures were not found to have any effect on vasovagal incidents. Conclusion: The determination of causes triggering vasovagal incidents seen during the application of spinal anesthesia, better patient information of regional anesthesia implementations and anxiety relief with preoperative anxiolytic treatment will help to eliminate potential vasovagal incidents.